Penggunaan Idol K-Pop sebagai Brand Ambassador Produk Skincare Lokal - Levina Fidelia; Kezia Kathalien; Celine Angela (CV. ULIL ALBAB CORP, 2024)
Korean Wave has now spread to various countries in the world including Indonesia, ranging from K-food, K-Pop, K-Drama, to K-Beauty. Almost everyone nowadays wants to have glowing skin like the K-Pop idols, that's why nowadays a lot of people use treatments for their skin using products from South Korea with the desire to have glowing skin like K-pop idols. Therefore, today many local skincare products want to compete with products from South Korea to create products that can make the skin brighter, and to be more in demand many local skincare companies use K-Pop idols as brand ambassadors.